Survey on The Factors Affecting the behavior (Attitude) of the National Consumers in Selecting Proper Airlines - fatemeh yavarigohar (مطالعات مدیریت بهبود و تحول, 2005)
Consuming behavior of consumer  is  under the  influence  of such factors  as  cultural,  social,  personal  &  psychological  factors.  This article emphasizing on psychological factors, generally tries to survey the factors affecting consumers'  attitude in selecting proper airlines (Emirates & Iranair Airlines to Dubai destination) and narrowly analyzes national consumers' attitude in this regard. The outcome of this thesis after having done lots of researches and with the use of Average method points to the  fact that Iranian passengers'  attitude about  such elements  as  flight  security,  flight management, proper flight hours, numerous flights, services offered during the flight and discounting  is  more  positive  about  Emirates  Airline  than  Iranair Airline. From the view point of expenses, the passengers almost have similar notions about both airlines. Finally Iranian passengers' attitude to Emirates Airline is more satisfactory than Iranair Airline.